Islamic real estate investment trusts in Malaysia - Rasheed,Saib M. (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2012)
This dissertation sheds light on the mechanism and practice of Islamic REITs in Malaysia. Islamic REITs have not received adequate attention from researchers in the field of Islamic banking and finance, which the researcher believes is an important area that needs more consideration. Structurally, there is no substantial difference between Islamic REITs and conventional REITs. Islamic REITs differ from their conventional counterpart mainly with regards to the former being required to adhere to Islamic investment guidelines and Sharf'ah principals related to formation and operations.The researcher made use of the comparative analytical approach with the aid of available data in the form of books, journals and reports as well as internet databases.The researcher observes that the Malaysian practice of both conventional and Islamic REITs have proven to be quite successful. Islamic REITs typically have relatively stable cash flows since almost all of their revenue is generated through rental payments. Islamic REITs also offer diverse advantages resulting from the establishment of Sharf' ah compliant portfolios of high quality real estate with varying tenancy lengths and geographical locations. The research discussed some examples from the Islamic REITs in the market, and made a number of recommendations for enhancing the operation of Islamic REITs and their effectiveness. The researcher believes the Guidelines for Islamic RE!Ts need to be more restrictive of tenants who engage in mixed activities. Also, those guidelines should emphasize on the purification of the revenues that are obtained from such activities. Regarding the practical implementation of Islamic REITs, the researcher recommends further studies to be conducted on this topic.